2018
DOI: 10.1007/s11229-018-1815-7
|View full text |Cite
|
Sign up to set email alerts
|

An efficient coding approach to the debate on grounded cognition

Abstract: The debate between the amodal and the grounded views of cognition seems to be stuck. Their only substantial disagreement is about the vehicle or format of concepts. Amodal theorists reject the grounded claim that concepts are couched in the same modality-specific format as representations in sensory systems. The problem is that there is no clear characterization of (modal or amodal) format or its neural correlate. In order to make the disagreement empirically meaningful and move forward in the discussion we ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 108 publications
0
2
0
1
Order By: Relevance
“…This would explain why some studies reported strong evidence for the involvement of modal representations during language processing, whereas others do not (for an overview, see Kaup et al, 2015 ; Kaup & Ulrich, 2017 ; see also Berndt et al, 2018 , 2020 ; Ostarek & Hüttig, 2017 ; Schütt et al, 2022 , 2023 ). Although the hybrid hypothesis has become popular in recent years (e.g., Binder & Desai, 2011 ; Dove, 2009 , 2011 , 2022 ; Wajnerman Paz, 2018 ; Zwaan, 2014 ), a systematic investigation of the factors that influence which type of representation gains the upper hand during comprehension and production is still missing.…”
Section: Languagementioning
confidence: 99%
See 1 more Smart Citation
“…This would explain why some studies reported strong evidence for the involvement of modal representations during language processing, whereas others do not (for an overview, see Kaup et al, 2015 ; Kaup & Ulrich, 2017 ; see also Berndt et al, 2018 , 2020 ; Ostarek & Hüttig, 2017 ; Schütt et al, 2022 , 2023 ). Although the hybrid hypothesis has become popular in recent years (e.g., Binder & Desai, 2011 ; Dove, 2009 , 2011 , 2022 ; Wajnerman Paz, 2018 ; Zwaan, 2014 ), a systematic investigation of the factors that influence which type of representation gains the upper hand during comprehension and production is still missing.…”
Section: Languagementioning
confidence: 99%
“…The considerations above reveal how the psychological reality of different types of representational formats has been largely accepted in cognitive psychology (albeit this acceptance is typically implicit). It is further notable that this view has recently even found its way into related disciplines such as philosophy of mind (e.g., Butterfill & Sinigaglia, 2014 ; Camp, 2009 ; Wajnerman Paz, 2018 ) and cognitive neuroscience (e.g., Leshinskaya & Caramazza, 2016 , see also Kuhnke et al, 2022 ). Yet it remains the case that the relationship between these formats and their functions for cognition is intensively debated, especially in the literature on the human conceptual system (e.g., Barsalou, 2016 ).…”
mentioning
confidence: 99%
“…Кроме того, не так давно обнаружилось, что многие эмпирические данные, поддерживающие укорененный подход, не специфичны для него и согласуются также с репрезентативным подходом (Michel, 2021;Wajnerman, 2018). Эти факты стимулировали развитие гибридных подходов, использующих как воплощенные, так и репрезентативные представления Pulvermüller, et al 2014, Zwaan, 2014.…”
Section: Introductionunclassified